Streetchild vendors' perceptions and concerns regarding their working and family conditions - Hayuhay, Ever I Nessa F.; Pradez, Joyce Anne M.
ABSTRACT Eighteen (18) street child vendors, from the age range of 7-12 years, vending in Quezon City, were observed and interviewed to examine their perceptions and concerns regarding their working and family conditions. Data gathered were analyzed according to gender and age of the participants. The results showed that street child vendors continue to work not only because of their family?s economic condition, but also because of their family relationships. Hence, in order to address the issue of child labor, the condition of family life in the Philippines should be considered. For future studies, it is recommended to have a wider locale and a larger sample. Different forms of child labor may also be focused on, as well as an older age range.